Renal Function Predicts Outcomes in Patients with Ischaemic Stroke and Haemorrhagic Stroke - Katarzyna Snarska; Katarzyna Kapica-Topczewska; Hanna Bachórzewska-Gajewska; Jolanta Małyszko (Karger Publishers, 2016)
Background/Aims: We evaluated renal function and the impact of renal function on in-hospital outcomes in patients with ischaemic and haemorrhagic stroke. Methods: We collected data from 766 patients with stroke; 637 (83.2 %) with ischaemic and 129 with haemorrhagic one. Results: The mean serum creatinine on admission in patients with both types of stroke, who died, was significantly higher than in those who survived. Multivariate analysis showed that independent predictors of mortality in patients with ischaemic stroke were: ischemic heart disease or prior myocardial infarction, diabetes, admission glucose and eGFR on admission. Also, multivariate analysis showed that independent predictors of mortality in patients with haemorrhagic stroke were: age and admission glucose. Conclusions: Patients with haemorrhagic stroke, in particular with acute kidney injury during hospitalisation had significantly worse outcomes than patients with ischaemic stroke. Assessment of kidney function is prerequisite to employ the necessary measures to decrease the risk of in-hospital mortality among patients with acute stroke. Appropriate approach to patients with renal dysfunction (adequate hydration, avoidance of nephrotoxic drugs, drug dose adjustment etc) should be considered as preventive and therapeutic strategies in the management of acute stroke.